What determines well-being in obesity? Associations with BMI, social skills, and social support - Dierk, Jan-Michael; Conradt, Matthias; Rauh, Elisabeth; Schlumberger, Pia; Hebebrand, Johannes; Rief, Winfried (Journal of psychosomatic research, 2006)
Theory and research suggest that the stigma associated with obesity has an impact on the development of social skills and social relationships which may be related to subjective well-being. The main objective was to clarify the associations between BMI (kg/m 2), social skills, social support and subjective well-being in a sample of obese subjects. Cross-sectional study of 226 obese adults (75 females and 151 males) from the general population between the ages of 19 and 74 [mean (SD), 46.9 (13.7) years]. Mean (SD) BMI of the subjects was 36 (5.3). Outcome measures: subjective well-being was measured by the Satisfaction With Life Scale (SWLS) and by the Positive And Negative Affect Scales (PANAS). Social support was assessed with scales of the Social Support Questionnaire F-SozU and social skills with a short form of the German Insecurity Questionnaire U-24. Hierarchical regression analysis showed that social support and social skill measures are relevant predictors of subjective well-being (with both independent and shared influences), while BMI is not. The obese people in our study neither differed from other comparison groups in their subjective well-being, nor did they report greater impairments in social skills or social support. BMI does not seem to be the major determinant of low subjective well-being in obesity. As in healthy controls, subjective well-being is principally associated with social skills and social support.